PELANGGAN DAN KARAKTERISTIKNYA DALAM PENDIDIKAN ISLAM - Irwasyah Irwasyah; Muchamad Suradji (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2021)
The development of the world in this era of globalization requires a lot of changes to a national education system that is better and able to compete in a healthy manner in all fields. One way that the Indonesian nation must do so as not to be left behind with other countries is to improve the quality of its education first. And one of the efforts to improve the quality of education is by paying attention to Total Quality Management (TQM). The Total Quality Management System is a management strategy aimed at instilling quality awareness in all processes within the organization. It is hoped that Islamic education will implement the TQM concept that is appropriate and in accordance with the goals and philosophy of Islamic education to improve the quality of educational services with quality insight so that it will be able to survive in accordance with the needs of the community without losing the main goal of Islamic education.